Achievements of the Center for International Forestry Research (CIFOR) 1998–2005 (Center for International Forestry Research, 2005)
This paper provides highlights of what the Center for International Forestry Research (CIFOR) has accomplished since January 1998. CIFOR achieved the results by entering into partnerships with governments, universities, NGOs, grassroots organisations and individual researchers were conducted through impact-oriented research and dissemination and training. The research is organised around three programmes focused on forests and livelihoods, environmental services and sustainable use of forests, and forests and governance.